Microwave synthesis of ZnO/rGO nanocomposites for enhanced degradation of dye / Fatin Saiha binti Omar - Omar, Fatin Saiha (2014)

(untitled)
Zinc oxide/reduced graphene oxide (ZnO/rGO) nanocomposites were successfully synthesized in the presence of diethylenetriamine (DETA) via a facile microwave assisted method. The x-ray diffraction (XRD) patterns of the ZnO/rGO nanocomposites reveal that obtained nanocomposite materials containing ZnO in hexagonal phase with wurtzite structure. The high-resolution transmission electron microscopy (HRTEM) images indicates that the prepared nanocomposites having ZnO nanorods, with an average length:diameter ratio of 10 and which is found to be deposited onto the rGO sheets. Under the irradiation of sunlight, the ZnO/rGO nanocomposites showed two-fold improved photocatalytic performance than that of unmodified ZnO towards the photodegradation of methylene blue. This may due to the high adsorbtivity of ZnO/rGO nanocomposite and synergistic effect raised between smaller ZnO nanorods and rGO matrix led to the improved photocatalytic activity. Further, the ZnO/rGO nanocomposites showed six-fold enhanced photocurrent response than that of bare ZnO nanorods. The excellent photocatalytic performance of the newly prepared ZnO/rGO nanocomposites could be a potential candidate for the photocatalysis and photoelectrochemical applications.